Efficacy of nanoparticle zinc oxide in the resistance of fungus Rhizoctonia solani causing black scurf disease in local potatoes - Wafaa J.R. Al-Zaidi; Amna M. Ali; Thamer A.A. Muhsen (Caspian Journal of Environmental Sciences)
This study was conducted to isolate and purify the causative agent of Black Scurf disease on potato crop and to test the efficiency of three concentrations (1, 2 and 3%) of zinc oxide nanoparticles (ZnO-PNs) and zinc oxide (ZnO) in controlling the fungus Rhizoctonia solani. The results of morphology and then molecular diagnosis by PCR technology showed that isolate R22 represents the fungus Rhizoctonia solani, which is the cause of potato black scurf disease. The isolate was registered in the gene bank under accession number OM83978. According to the results of laboratory inhibition exhibited that 3% nano-zinc oxide leads to the highest inhibition rate (85.9%) compared to the control group. Also, 3% zinc oxide showed inhibition rate of 43.71% compared to the control. The results of the pot treatments test showed that all of them had an effect in reducing the infection rate (%) and the severity of infection with the fungus R22. So that, the nano-zinc oxide treatment recorded the lowest rate (%) and severity of infection (11% and 4.73% respectively), followed by the fungicide (Ethidium bromide), which scored 22.22% and 18.33% respectively, while in the case of zinc oxide, we recorded 33.33% and 19.03%, respectively, compared to the control group (plant with R22). The results of the study of growth parameters (plant height, fresh weight, dry weight and number of leaves) also exhibited that the nano-zinc oxide treatment recorded a positive increase in growth parameters that amounted to 54, 24.33, 7.33 and 99.33% compared to the control group.